Mental Health-Friendly School St Mental Health-Friendly School Strategies: Psychological Intervention Approaches for Adolescent Mental Health in Educational Settings - Hikmah, Nurul Hikmah; Hamim, Hamim (Proceedings Conference Psychology and Flourishing Humanity, 2026)
Adolescents face increasing mental health challenges that affect their academic performance, social relationships, and overall well-being. Schools, as primary educational and socialization environments, play a critical role in supporting students’ psychological health. This paper explores strategies for developing mental health-friendly schools through targeted psychological intervention approaches. Drawing on recent research in educational psychology and adolescent development, the study highlights three key strategies: (1) fostering a supportive school climate through teacher training and peer mentoring, (2) integrating evidence-based mental health programs into curricula, and (3) strengthening collaboration between schools, families, and community mental health services. These strategies aim to promote resilience, early detection of emotional difficulties, and access to appropriate care. By analyzing case studies and best practices from various educational contexts, the paper demonstrates how proactive interventions can reduce stigma, enhance coping skills, and create inclusive learning environments. The findings suggest that adopting a holistic framework—combining prevention, intervention, and post-crisis support—significantly improves students’ mental health outcomes. This study provides practical recommendations for educators, policymakers, and mental health professionals to collaboratively design interventions that address the unique needs of adolescents. Ultimately, mental health-friendly schools are essential to fostering flourishing, resilient, and academically successful young people.